An Overview of the Innovations of the Companies and Allied Maters Act 2020: Expansions or Restrictions? - Temiloluwa Omidiji (African Journal of Law, Ethics and Education, 2022)
The Companies and Allied Matters Act 2020 was recently signed into law by President Muhammadu Buhari. The new Act primarily repeals the Companies and Allied Matters Act of 1990. The Act is intended to bring Nigeria's corporate sector up to date and in line with global best practices. This paper looks at the Act's novelties and how it compares to the old Act to fulfill international standards. In addition, the paper examines and summarizes regulatory organizations' statutory obligations to develop and enforce a code of corporate governance in Nigeria and the role regulatory bodies play in enhancing Nigeria's business environment and the impact of their operations on Nigerian enterprises. This paper examines the Act's prospects and difficulties for implementation. The paper adopts the doctrinal method, drawing on both primary and secondary sources, and concludes that CAMA's innovation will improve the ease of doing business and allow her to compete with her peers around the world. The paper ends with recommendations on how to implement likely challenges the stakeholders of the new legislation may encounter in the course of enforcing the law. The paper agrees that there are expansions and restrictions in company administration under the new CAMA 2020.